La fabrique d’un saint missionnaire jésuite dans la longue durée (xviie, xviiie et xixe siècles) : Pedro Claver (1580-1654) entre rhétorique, théologie et histoire - Gérard Neveu (Les Dossiers du GRIHL)
Historical studies about “legends” in the Modern and Contemporary Period (17th-20th centuries) were limited by stereotypes. Our analysis of a corpus of hagiographic sources about Pedro Claver (1580-1654), a Catalan Jesuit in mission in South America considered as the “apostle of black slaves”, emphasizes religious, political and social issues linked to the Canonization of the Saint by Leon XIII in 1888 and the context of ideological competition and struggle between Rome and Anglo-Saxon powers about the abolition of slavery. The aim of that comparative textual and iconographic study is to “historicize” and put into context these rhetorical constructions. It also makes aware of the limits of hagiographical discourse.